Bridging Cultures, Enhancing Performance: Intercultural Communication Challenges of Thai SMEs in the Special Economic Zones - Chung, Ji Hye Jaime; Min, Joshua Youngbin (ASEAN Journal of Management & Innovation, 2024)
This exploratory study investigates Thai SME employees’ perceptions on intercultural communicative challenges and gain insights on what they justly need in order to perform effectively when engaging with foreign clientele. Data were collected from SMEs in the north-eastern region of Thailand via interviews and survey questionnaire. The study found that there were certain issues regarding intercultural communication that drove the employees to shy away from communicating with foreign clientele. Adding to that, lack of effective programs, unmotivated employees due to little or no incentives, and negative perceptions toward time-consuming training courses all hindered employees in this particular region from gaining practical knowledge on intercultural communication. Strongly supported by the Thai government, businesses in the special economic zones are growing domestically and internationally; thus, it is crucial for the employees to be armed with intercultural competency. This study adds to the discussion on intercultural trainings employees justly need as well as how to implement a positive learning culture when stakeholders are demotivated.